Diversity of Auchenorrhyncha (Hemiptera: Cicadellidae: Delphacidae) associated with Vicia villosa in southern Buenos Aires province, Argentina - Paradell, Susana Liria; Defea, Bárbara Soledad; Dughetti, Arturo Carlos; Zarate, Alberto; Marino de Remes Lenicov, Ana Maria (2018)
Among the Hemiptera, the Auchenorrhyncha are well known owing to their phytosanitary relevance since the group includes pathogen vector species able to damage commercial crops. Vicia villosa Roth (Fabaceae) is a fodder plant species, mainly distributed in central Argentina. Previous contributions have shown that V. villosa is colonized by diverse species of Auchenorrhyncha, either naturalized or native to valley of Colorado River area, in southern Buenos Aires province. To date, the only information about the species of hoppers associated with Vicia has come from preliminary field observations. The dearth of demographic knowledge about these phytophagous insects associated with this crop in Argentina motivates the study. The aims of this work were: 1) to characterize the diversity of the species of Auchenorrhyncha associated with V. villosa and 2) to determine the seasonal fluctuation of the most abundant species in relation to local weather variables and crop phonological phases. The study was conducted in Vicia plots located at EEA INTA Hilario Ascasubi (S 39° 23′ 36″ -W 62° 37′ 59″, 15 m.a.s.l.) southern Buenos Aires province. The specimens were collected with a sweep net during 2 yr (2009 and 2011). Weather variables were recorded using a meteorological station located at the sampling site. To measure species richness and community diversity we calculated both Margalef (DMg) and the Simpson (D) indexes, and also, the Relative Importance Index (RII). The relationships between population densities of the leafhoppers, Paratanus exitiosus (Beamer) and Agalliana ensigera Oman (Cicadellidae), with weather variables were analyzed through simple and multiple linear regression. A total of 17 species were associated with V. villosa crops in Argentina, of which 15 belong to the Cicadellidae and 2 to the Delphacidae. Abundance and species richness were higher in 2009 than in 2011. In general, the results of the Margalef index showed that species richness was higher in 2009, while Simpson Index (D) indicated a higher dominance in 2011 than in 2009. The species, P. exitiosus and A. ensigera, stood out for their abundance, frequency and phytosanitary relevance during the sampling period. Both species presented population increases since Nov coinciding with different phenological phases of the crop and the maximum density of the canopy. Additionally, the population density of P. exitiosus showed strong dependence on the hydric balance and photoperiod, while A. ensigera was influenced by Degree-days10 and hydric balance. Vicia villlosa was a new host-plant record for 15 species. Buenos Aires province was cited as a new distribution record for 2 species.